Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/su13063359
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Key Watershed Characteristics That Affect the Biological Integrity of Streams in the Han River Watershed, Korea

Abstract: Understanding the complex human and natural processes that occur in watersheds and stream ecosystems is critical for decision makers and planners to ensure healthy stream ecosystems. This study aims to characterize the Han River watershed in Korea and extract key relationships among watershed attributes and biological indicators of streams using principal component analysis (PCA) and self-organizing maps (SOM). This study integrated watershed attributes and biological indicators of streams to delineate the wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…When it comes to comprehensive evaluation, SOM is frequently used to analyze multifactor datasets and solve complex classification problems, such as a comprehensive analysis of tourist motivation and behavior in protected areas [ 38 ]. SOM can also be used to investigate relationships between research elements, such as correlations between river ecological indicators [ 39 ], pattern associations between different environmental conditions and physiological responses [ 40 ], and links between residents' lifestyles and their choice of residence within the city [ 41 ]. Using SOM to create a parametric building model can optimize the architectural design scheme [ 42 ].…”
Section: Relevant Researchmentioning
confidence: 99%
“…When it comes to comprehensive evaluation, SOM is frequently used to analyze multifactor datasets and solve complex classification problems, such as a comprehensive analysis of tourist motivation and behavior in protected areas [ 38 ]. SOM can also be used to investigate relationships between research elements, such as correlations between river ecological indicators [ 39 ], pattern associations between different environmental conditions and physiological responses [ 40 ], and links between residents' lifestyles and their choice of residence within the city [ 41 ]. Using SOM to create a parametric building model can optimize the architectural design scheme [ 42 ].…”
Section: Relevant Researchmentioning
confidence: 99%
“…The HRB (126 • 24 -129 • 02 E, 36 • 30 -38 • 55 N) is the largest basin in Korea with an area of 26.219 km 2 , accounting for approximately 27% of the entire country area [31,37]. The Han River is approximately 494 km long, and consists of 920 rivers and streams, including 19 national rivers and streams and 901 local rivers and streams [38]. The average annual precipitation in the HRB is approximately 1300 mm, and the basin witnesses a monsoon climate, with approximately 70% of the precipitation concentrated in summer (July-September) [31].…”
Section: Study Areamentioning
confidence: 99%
“…Regarding the water use status in the HRB, domestic purposes represent the largest proportion (46.6%), followed by agricultural purposes (38.5%), and industrial purposes (14.9%) [42]. The land use status in the HRB comprises forests (68.9%), farmlands (14.9%), cities (8.3%), and other areas (7.9%) [38]. In this study, Yeongwol 2 (S-1), Chungju Dam (S-2), Dal Stream 4 (S-3), Seom River 4-1 (S-4), Gang Stream (S-5), Gangsang (S-6), Soyang River (S-7), Uiam Dam (S-8), Sambong-ri (S-9), Kyeongan Stream (S-10), Paldang Dam (S-11), Noryangjin (S-12), Gayang (S-13), and Imjin River (S-14) were selected as main water quality monitoring sites in the Han River water quality monitoring network operated by the Ministry of Environment (MOE) (Figure 1).…”
Section: Study Areamentioning
confidence: 99%
“…They suggested that the aquatic ecosystem be investigated using data such as flow rate and river depth. Park et al [19] characterized the Han River watershed in Korea and extracted key relationships among the watershed attributes and biological indicators of the streams. They used biological indicators of the streams to determine the biological status of the watershed and stream.…”
Section: Introductionmentioning
confidence: 99%
“…They used biological indicators of the streams to determine the biological status of the watershed and stream. Park et al [19] analyzed the correlation between river morphological factors and water quality factors. Woo et al [20] conducted a study on whether the flow affects water quality and aquatic health by simulating the flow using SWAT.…”
Section: Introductionmentioning
confidence: 99%